2007
DOI: 10.1007/s10535-007-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and plant regeneration of Abelmoschus esculentus through suspension culture

Abstract: A simple and reliable protocol for regeneration of okra through somatic embryogenesis from suspension cultures has been developed. Embryogenic callus was obtained from hypocotyl explants cultured on media with Murashige and Skoog (MS) salts, Gamborg (B5) vitamins, 2.0 mg dm -3 2,4-dichlorophenoxyacetic acid (2,4-D), 1.0 mg dm -3 naphthaleneacetic acid (NAA), 25 mg dm -3 polyvinylpyrrolidone and 30 g dm -3 sucrose. More number and high frequency of healthy embryoids appeared individually in suspension culture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In this study, 30 g sucrose was found to be the best for embryogenic callus induction. These results were similar to those reported by Ganesan et al (2007) in okra and in black iris by Shibli and Ajlouni (2000). For successful regeneration of synthetic seeds from the somatic embryos, good quality embryogenic callus is essential (Ganesan and Jayabalan 2004).…”
Section: Resultssupporting
confidence: 93%
“…In this study, 30 g sucrose was found to be the best for embryogenic callus induction. These results were similar to those reported by Ganesan et al (2007) in okra and in black iris by Shibli and Ajlouni (2000). For successful regeneration of synthetic seeds from the somatic embryos, good quality embryogenic callus is essential (Ganesan and Jayabalan 2004).…”
Section: Resultssupporting
confidence: 93%
“…These results show that cytokinins (BA and zeatin) have stimulatory roles for plantlet development from embryogenic cell suspension cultures of watershield. A stimulatory role for cytokinin in plantlet development from somatic embryos was also reported for Abelmoschus esculentus (Ganesan et al 2007), and Ophiorrhiza prostrata (Martini et al 2007). …”
Section: Effects Of Activated Charcoal and Zeatin On Plantlet Developmentioning
confidence: 58%
“…Tissue culture-based direct shoot regeneration from cotyledon and cotyledonary node explants (Mangat and Roy, 1986 ), and regeneration of okra plants from callus tissue derived from cotyledonary axil (Roy and Mangat, 1989 ) are known. Further, Ganesan et al ( 2007 ) have reported plant-regeneration protocol through somatic embryogenesis from suspension culture; while Anisuzzaman et al ( 2008a ) developed a protocol for mass in vitro propagation using meristem culture for disease-free plant production. Anisuzzaman et al ( 2008b ) have optimized a viable protocol for indirect shoot organogenesis of okra, from leaf-disc and hypocotyl via callus phase.…”
Section: Transformation Protocols and Transgenic Development In Okramentioning
confidence: 99%